(untitled) (Asian Journal of Social Science Studies, 2022)
With the continuous expansion of the market scale of online shopping, the contradiction between merchants, platforms and consumers has gradually become prominent, which is manifested in the increasing number of online shopping disputes in the courts. The determination of jurisdiction is the starting link before the dispute enters the litigation, which involves the orderly conduct of civil litigation and is related to the interests of the parties. This paper attempts to analyze the causes of the jurisdictional issues of online shopping contract disputes through the investigation of the jurisdictional decisions, explore the shortcomings of existing jurisdictional provisions in online shopping contract disputes, improve the jurisdictional system of online shopping contract disputes, and explore possible legal optimization paths, so as to provide theoretical support for legislation and justice.